Healthcare Workers Knowledge, Attitude, and Availability of Facilities Toward Compliance Hand Hygiene - Richa Noprianty; Gendis Kintan Dwi Thahara (Indonesian Journal of Global Health Research, 2019)
Failure to perform good hand hygiene is considered as an major cause of Healthcare Associated Infections (HAIs). From the WHO data, compliance rate of nurses hand hygiene activity at the United States is about 50%, Australia 65% while in Indonesia 47%. This study aims to determine healthcare workers knowledge, attitude, and availability of facilities toward that affect hand hygiene compliance. This research method is analytical descriptive with cross-sectional approach. The object of data collection is an healthcare workers (nurse, doctor, and pharmacy) at General Hospitalin West Java as many as 51 samples. Sample selection using stratified sampling method with research instrument in the form of questionnaire and observation sheet about knowledge and attitude to hand hygiene adopted from WHO. The results of this study that obtained in the group of nurse were 48.6% doing imperfect hand hygiene and group of doctor respectively 80.0% and pharmacy were 100.0%. In terms of nurses knowledge about hand hygiene is 59.5%, doctor80.0% and pharmacy 50.0%. In terms of attitudes about the implementation of hand hygiene, the nurses group is 48.6%, doctors respectively 40% and pharmacy 50.00% have a positive attitude. In terms of facilities is 40.5% nurses stated available, doctors 20% and pharmacy 0.00%. There was a significant relationship between hand hygiene with knowledge (p = 0,019), attitude (0.004) and hand hygiene facility (p = 0.040). Keywords: attitude, hand hygiene, health care, knowledge